ANALISIS IMPLEMENTASI REFORMASI BIROKRASI DALAM MEREALISASIKAN GOOD GOVERNANCE DAN PENCAPAIAN TARGET MILLENIUM DEVELOPMENT GOALS (STUDI KASUS PADA PEMERINTAH KOTA YOGYAKARTA) - Wiwin Kurniasari (Jurnal Akuntansi, 2016)
This report aims to review the implementation of bureaucracy reform in realizing good governance and the target mdgs the city government yogyakarta .This research is considered as policy research associated with bureaucracy reform based on the minister of utilization state apparatus and bureaucratic reform no. 11 years 2011 .The research is municipal yogyakarta that is city administration reward challenged the highest in the management of governance se-indonesia given by the indonesian government index ( igi ) since 2012-2014 with with get a rata-rata 6,8 index governance .The data in this research consisting of primary and secondary data .The method of analysis that used in this research is descriptive analytical , analysis techniques use also content analysis. The research results showed that the implementation of good governance of the Government of the city were in accordance with the regulations of the Minister for Administrative Reform and the bureaucratic State apparatus No. 11 in 2011. Keyword: good governance, indonesian government index